Low-cost gelatin/collagen scaffolds for bacterial growth in bioreactors for biotechnology - Pompa-Monroy, Daniella Alejandra; Vera-Graziano, Ricardo; Dastager, Syed G.; Perez-Gonzalez, Graciela Lizeth; Bogdanchikova, Nina; Iglesias, Ana Leticia; Villarreal-Gomez, Luis Jesus (Applied Microbiology and Biotechnology, 2025)
A wide array of pharmaceutical and industrial products available in today's market stems from bioreactors. Meeting the escalating demand for these products necessitates significant enhancements in biotechnological processes. This study focuses on developing cost-effective scaffolds designed explicitly for use within bioreactors, employing commonly used polymers such as gelatin and collagen. Bacterial proliferation assays involving Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa were conducted to assess the effectiveness of these scaffolds. The scaffolds were produced by electrospinning polymeric solutions with varying concentrations of gelatin and collagen and were characterized using scanning electron microscopy, Fourier transform infrared spectroscopy, differential scanning calorimetry, and thermogravimetric analysis. Results revealed that scaffolds with 15% gelatin increased the 24-h proliferation of S. aureus, P. aeruginosa, and E. coli by 52%, 35%, and 20%, respectively. In the case of E. coli, scaffolds with lower gelatin concentrations (1-10%) were more effective, leading to 35-55% proliferation growth. These findings highlight the potential application of gelatin/collagen scaffolds in fabricating industrial products derived from these bacteria.
Keywords: Bacterial cell proliferation; collagen; gelatin; Polymeric electrospinning; scaffolds